Sistem Kepercayaan Paganisme Arab Pra-Islam dan Transformasinya Pasca Kenabian - Shaleh Afif (Khulasah : Islamic Studies Journal, 2025)
This study examines in depth the system of pagan beliefs in pre-Islamic Arabia and the profound transformation that occurred following the Prophetic mission of Muhammad. Employing a qualitative historical approach grounded in classical Islamic historiography as well as contemporary scholarly works, this research systematically analyzes the theological structure, ritual expressions, and socio-political functions embedded within Arabian paganism. The findings demonstrate that pre-Islamic paganism was not merely a simple polytheistic belief system; rather, it was deeply intertwined with tribal authority, economic networks, and constructions of social identity. Although Allah was acknowledged as the supreme deity, idols operated as intermediaries in religious rituals, particularly those centered around the Ka'bah. The transformation initiated after the advent of prophethood was marked by a revolutionary theological shift through the doctrine of tawhid (monotheism), accompanied by a gradual restructuring of social and cultural norms. Islam dismantled idolatrous practices while retaining and purifying certain existing traditions, thereby establishing a new monotheistic paradigm that fundamentally reshaped Arabian civilization. This study contributes to broader discussions concerning religious transformation and socio-theological change in early Islamic history.